Новый род полорогих из среднего плиоцена Восточной Европы - Короткевич, Е.Л. (Вестник зоологии, 1975)
A fragment of skull with a horny rod of rather big hollow-horned ruminant is found in old alluvial, sandy-pebbled deposits in the valley of the Kuchurgan river near the village of Novopetrovka, Velikaya Mikhailovka district, Odessa region. Hollow-horned ruminants occur extremely rarely in the composition of the Kuchur- gan fauna the age of which is determined by the beginning of the Middle Pliocene. Peculiarities of structure of rather long (to 300.0 mm) straight, comparatively massive horny rods, with the interior and posterior-external keels with a cross-section of irregular-oval shape and served as a basis for describing a new genus and species of the subfamily Bovinae.